Autonomic nervous system: Anatomy and physiology [OTONOM SINIR SISTEMI: ANATOMI VE FIZYOLOJISI] - (:unkn) unknown (My University, 1995)
Autonomic nervous system is composed of various numbers of ganglions, plexuses and a series of cerebrospinal nuclei and nerves which are responsible of vegetative functions of the body. To understand the clinical syndromes associated with autonomic nervous system and to evaluate them the anatomy and physiology of the ANS should be well understood. Therefore it's important to know the recent advances about the central autonomic network besides the sympathetic and parasympathetic systems.
Keywords: Autonomic nervous system